2011
DOI: 10.1017/s0960258511000110
|View full text |Cite
|
Sign up to set email alerts
|

Cathodic amelioration of the adverse effects of oxidative stress accompanying procedures necessary for cryopreservation of embryonic axes of recalcitrant-seeded species

Abstract: Several of the procedures necessary for cryopreservation of excised zygotic embryonic axes are known to be accompanied by emission of damaging levels of reactive oxygen species (ROS). These have been shown to be associated with shoot apical meristem necrosis, curtailing subsequent axis development to root production only, particularly for tropical/subtropical recalcitrant-seeded species. Here we report on the application of the principles of electrochemistry in the generation of strongly reducing, high pH cath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
70
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(76 citation statements)
references
References 56 publications
4
70
0
2
Order By: Relevance
“…The data also point to the value of characterising the type and quantity of oxidative stress associated with dehydration to particular WCs, as exogenous antioxidant application may be required to facilitate post‐cryo survival ( e.g ., Berjak et al . ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The data also point to the value of characterising the type and quantity of oxidative stress associated with dehydration to particular WCs, as exogenous antioxidant application may be required to facilitate post‐cryo survival ( e.g ., Berjak et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…Additionally, these data suggest that recalcitrant seeds of monocotyledonous/herbaceous and dicotyledonous/woody species may differ in terms of detecting and coping with ROS. The data also point to the value of characterising the type and quantity of oxidative stress associated with dehydration to particular WCs, as exogenous antioxidant application may be required to facilitate post-cryo survival (e.g., Berjak et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…TAA activity was measured on 50 mg (per replicate, n = 3) of spores, which were ground in liquid nitrogen with 10 mg polyvinylpyrrolidone and 1 mL phosphate extraction buffer as described by Berjak et al (2011). The contents were transferred into chilled Eppendorf tubes, which were vortexed at 5 min intervals for 15 min and centrifuged at 14,000 rpm at 4 °C for 1 h. The supernatant was then decanted and placed on ice.…”
Section: Determination Of Total Aqueous Antioxidant Activitymentioning
confidence: 99%
“…This entails excision of the embryos/axes from the seeds which imposes the first of the oxidative stresses inflicted during processing for, and retrieval from, cryostorage. [However, as the subject of this review focuses on the implications of the lack of desiccation tolerance, excision-related oxidative injury as first suggested by Goveia et al (2004) and studied in detail by Roach et al (2008), Whitaker et al (2010), Berjak et al (2011), Naidoo et al (2011), and Varghese et al (2011), will not presently be considered further.…”
Section: Traits Of Recalcitrant Seedsmentioning
confidence: 99%
“…In this regard, Bai et al (2011) have reported that nitric oxide enhances survival of A. toxicaria axes and Pukacka et al (2011) have found that provision of selenium protects Acer saccharinum axes subjected to desiccation. The use of cathodic water (produced by electrolysis of a dilute solution of calcium- and magnesium chloride) that has strong reducing properties, is promising in terms of ROS quenching (Berjak et al, 2011). …”
Section: Traits Of Recalcitrant Seedsmentioning
confidence: 99%